Genus Donax in the Peruvian coast (Bivalvia: Telllnoidea) - Paredes, Carlos (2001)
In the present paper the species of Donax Linnaeus, 1758 in Peru are reviewed. The presence of 7 out of the 11 species is confirmed: D. asper Hanley. 1845; D. caelatus rothi Coan, 1983; D. obesulus Reeve, 1854; D. carinatus Hanley, 1843; D. transversus Sowerby 1,1825; D. californicus Conrad, 1837 and D. marincovichi Coan, 1983; in addition, one is recorded for the first time (D. punctatostriatus Hanley, 1843) in Peruvian waters. Information on the distribution geographical and some ecological relations is presented.